Les codes du factice dans Big Fish de Tim Burton - Anne-Marie Paquet-Deyris (Sillages Critiques)
Tim Burton’s Big Fish closely mirrors the structure of the initiation tale. The film unfolds as a visual variation on the art of storytelling and on the way it is passed on. A son is striving to understand his dying father who happens to be a fantastic story-teller. And as he’s sitting by the myth-maker’s bedside and as the credits unwind, the spectator is already steeped in the southern tall tale universe. The opening sequence visually inscribes on screen the grotesque and magical figures of its hyperbolic stories. The characters’ tricks already foreground their consummate artistry and some essential, creative cunning allowing real and imaginary sequences to combine. In the final scenes, the father’s voice-over fuses with the son’s, who eventually inherits the inventive and circumvoluted narrative power. The handing-over process between the two men registers on screen in a series of visual and narrative conjuring tricks Philippe Rousselot’s sumptuous cinematography greatly enhances.